Alternative Vine Management Programs for Fresh-Market Potatoes. (October 2018) - Lemke, Matthew J.; Colquhoun, Jed B.; Heider, Daniel J.; Rittmeyer, Richard A.
Abstract: Economically solvent fresh-market potato production is predominantly dependent on the ability to efficiently produce consistent tuber quality and high yield, and the ability to meet first-to-market demand with early-season potatoes. Unfortunately, these two qualifiers often work against each other in terms of production management. In response, we studied integrated potato vine management programs that support timely early-season potato harvest. Vine management with a flail chopper, roller, and flame burner used alone or followed by diquat was evaluated when initiated 21 or 14 d prior to harvest in 2015 and 2016. Potato varieties included 'Yukon Gold' and 'Dark Red Norland'. Potato leaf and stem management, as well as tuber skinning, stolon separation, grade, and yield were quantified. Among mechanical methods, potato leaf and stem management were poor when vines were rolled or mowed but better when flail chopped. In general, vine management and tuber skin set was better when treatments were initiated 21 d prior to harvest as opposed to 14 d. Vine management, tuber skin set, and yield were comparable when potato vines were flail chopped followed by flame burning and where diquat was applied twice, offering a viable program for smaller scale or organic production.